Pengaturan Hak Asuh Anak Pada Kasus Perceraian Akibat Kekerasan Dalam Rumah Tangga (KDRT) - Brazilia Emanuel Rajamuda Napitupulu; Ni Made Ari Yuliartini Griadhi (CV. Lenggogeni Data Publishing, 2024)
The study aims to: 1) increase our understanding of post-divorce child custody arrangements; 2) illuminate the variables taken into account when determining child custody in cases involving domestic abuse; and 3) make clear the legal framework controlling child custody during the divorce proceedings. This essay makes use of normative legal research techniques, which center on the examination of relevant legal norms.